The Significance of Normativity: Studies in Post-Kantian Philosophy and Social Theory - Thomas Presskorn-Thygesen (Copenhagen Business School (CBS), 2017)
This dissertation examines the concept of normativity through a series of studies in post- Kantian philosophy and social theory. The overall aim is to analyse the historical as well as systematic relevance of the concept of normativity to modern philosophy and to the methodological challenges of social theory. In pursuing this overall research agenda, the dissertation contributes to a number of specific research literatures. Following two introductory and methodological chapters, Chapter 3 thus critically examines the analysis of normativity suggested in the recent attempts at transforming the methods of neo-classical economics into a broader form of social theory. The chapter thereby contributes to the critical discourses, particularly in philosophy of science, that challenge the validity of neo-classical economics and its underlying conception of practical rationality. In examining the practical philosophies of Kant and Hegel, Chapter 4 substantiates and collects the numerous, specific insights on normativity, practical rationality and autonomy that have been generated by the so-called `post- Sellarsian' reading of German Idealism. The chapter thereby contributes not only to this particular branch of philosophical exegesis, but also to the social theoretical concern with the conceptions of autonomy and agency that have influenced European modernity. Chapter 5 examines the social theoretical transfiguration of the problems of German Idealism that occurred in the works of Durkheim and Weber. It does so by situating Durkheim and Weber in the context of Neo-Kantian philosophy, which prevailed among their contemporaries, and the chapter thereby reveals a series of under-thematised similarities not only with regard to their methodological positions, but also in their conception of social norms. Chapter 6 employs the late Wittgenstein's much-debated rule-following considerations to recapitulate the significance of normativity to philosophy and social theory; in this way the chapter shows a wider import of the rule-following considerations that go beyond the strict mathematical and epistemological perspectives most often analysed in the Wittgenstein scholarship related to this topic.
hdl:10398/9473
Keywords: 650